Pembelajaran Sains Berbasis Eksperimen Pewarna Alami dan Buatan untuk Anak PAUD (Aku dan Warna) - Ima Ismail; Wa Ode Rizka Fauziah Ali (Pusat Riset dan Inovasi Nasional, 2021)
This study aims to determine the effectiveness of science learning based on experiments using natural and artificial dyes in improving early childhood color recognition skills and science process skills. Early Childhood Education (ECE) requires learning activities that are concrete, enjoyable, and based on direct experiences so that children can actively understand concepts through exploration. Color-mixing activities were chosen because they can stimulate curiosity, creativity, observation skills, and children’s communication abilities. The study employed a quantitative approach with a one-group pretest-posttest design. The subjects consisted of 20 children aged 5–6 years in an ECE institution. The experiment was conducted over four meetings under the theme “Me and Colors,” using natural dyes such as turmeric, pandan leaves, butterfly pea flowers, and dragon fruit, as well as safe artificial dyes for children. Data were collected through observation, documentation, and child development assessment sheets. The results showed an improvement in children’s color recognition skills from the “Beginning to Develop” category (55%) in the pretest to “Developing as Expected” and “Very Well Developed” (80%) in the posttest. Science process skills, creativity, fine motor skills, and socio-emotional development also improved through experimental and group activities. This learning approach proved effective in creating active, interactive, and enjoyable learning experiences in early childhood education.